Los condicionamientos de la apócope en los textos castellanos antiguos - Moreno Bernal, Jesús (Revista de Filología Románica, 2004)
With this study the author sets out to describe to the agreements of the alternance between total forms and forms reduced in some medieval texts and to need the relation between the graphical systems these texts and the apocope. For it, it will be necessary to find a methodologic point of view that considers the phonetic, phonetic syntactic factors and morphologic that determines the alternance. It will be necessary to consider the circunstances that favor and that prevent the apocope. It will be precise also to locate this phenomenon within the context of the high degree of variation that admitted Castilian the medieval one. Also it will be necessary to distinguish between verse texts and prose texts, because the metric exigencies can have a determining influence.